THE ANALYSIS OF CALCULATION, SETTLEMENT AND REPORTING: OF INCOME TAX ARTICLE 23 IN PT. POLYTECH INDONESIA IN 2016 - Octavania, Hilda Yolanda; Manurung, Jean P.; L.Tobing, Suzanna Josephine L.Tobing (Fundamental Management Journal, 2017)
This study aims to determine whether the implementation and recording of transactions related to Income Tax Article 23 at PT. Polytech Indonesia has been correct and in accordance with applicable tax laws.The data used comes from the primary data of PT. Polytech Indonesia in tax period February to October 2016. The research methodology used is qualitative analysis. Particularly for quantitative data analysis techniques is done by analyzing data that has been obtained to obtain a broader meaning by calculating and interpreting the data that have been analyzed is connected with existing theory. The conclusion that can be taken is that PT. Polytech Indonesia has implemented correctly and in accordance with applicable tax laws and within the organizational structure of PT. Polytech Indonesia, in carrying out duties and wawenang already done very well Suggestion from author to be useful for PT. Polytech Indonesia is to add competent staff so that in preparing taxation obligations in the implementation of calculation, remittance and reporting of Income Tax Return of Article 23 in order to always follow the regulations of taxation with obedience and timely in the implementation, so as not to be subject to fines and sanctions that may harm the company.Keywords: Implementation and recording of transactions